Lessons Learned from Public and Private Contract Managers for Effective Local Government Contracting Out: The Case of New Jersey. Issue 9 (29th July 2017) - Kim, Soojin
ABSTRACT: To date, very few studies have explored practical strategies for exercising effective financial management of local government contracts through two main stakeholders' perspectives of the contracting system at the same time. Employing a series of semi-structured interviews with public officials and private contractors in New Jersey, this study attempts to fill this gap in the scholarship. The finding of this study suggests that government agencies should pay greater attention to competitive bids without favoritism, contract specificity, a statewide performance database, sufficient staffing with well-trained personnel, strong leadership, team-based structures, two-way communication, and evaluation based on both qualitative and quantitative values.